2013
DOI: 10.3727/096368912x657422
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Transplantation of Interneuronal Precursor Cells Decreases Anxiety-Like Behavior in Adult Mice

Abstract: The GABAergic system is critically involved in the modulation of anxiety levels, and dysfunction of GABAergic neurotransmission appears to be involved in the development of generalized anxiety disorder. Precursor cells from the medial ganglionic eminence (MGE) have the ability to migrate and differentiate into inhibitory GABAergic interneurons after being transplanted into the mouse brain. Thus, transplantation of interneuronal precursor cells derived from the MGE into a postnatal brain could modify the neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
2
12
2
Order By: Relevance
“…Likewise, aggressive behaviors were diminished in epileptic mice that received interneuron transplants to the adult hippocampus, but not the amygdala (32). Moreover, while transplantation to both structures reduced hyperactivity in adult epileptic animals, it did not produce some of the anxiolytic effects observed after transplantation to wild-type neonatal animals (72). This finding could be attributed to differences between the transplant recipients (epileptic versus wild-type), time of transplantation (adult versus neonate), and structures targeted (hippocampus and amygdala versus neocortex).…”
Section: The Clinical Potential Of Interneuron Transplantationmentioning
confidence: 92%
See 1 more Smart Citation
“…Likewise, aggressive behaviors were diminished in epileptic mice that received interneuron transplants to the adult hippocampus, but not the amygdala (32). Moreover, while transplantation to both structures reduced hyperactivity in adult epileptic animals, it did not produce some of the anxiolytic effects observed after transplantation to wild-type neonatal animals (72). This finding could be attributed to differences between the transplant recipients (epileptic versus wild-type), time of transplantation (adult versus neonate), and structures targeted (hippocampus and amygdala versus neocortex).…”
Section: The Clinical Potential Of Interneuron Transplantationmentioning
confidence: 92%
“…At 30 and 60 days after transplantation, but not 15 days, transplant recipients were less likely to avoid exposed areas of an elevated plus maze, a behavior indicative of diminished anxiety (72). Likewise, aggressive behaviors were diminished in epileptic mice that received interneuron transplants to the adult hippocampus, but not the amygdala (32).…”
Section: The Clinical Potential Of Interneuron Transplantationmentioning
confidence: 99%
“…It will be interesting to investigate whether interneuron transplantation can modify fear memory resiliency, which bears strong therapeutic implications for patients suffering from posttraumatic stress disorders. Interestingly, MGE cell transplants have been shown to reduce anxiety levels in WT animals (Valente et al, 2013). …”
Section: Disease-modifying Properties Of Mge Transplantsmentioning
confidence: 99%
“…Neural precursor cells from the medial ganglionic eminence (MGE) of the telencephalic region in the developing brain are responsible for producing most of the inhibitory interneurons in both the cortex and the hippocampus of the mature brain [3, 4]. When transplanted into the newborn cortex, these cells are able to migrate and integrate into the circuitry of the host brain, forming functional synapses that modify the inhibitory input [35]. In the central nervous system, GABA-mediated inhibition is critical for controlling synaptic circuits involved in the modulation of anxiety [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the central nervous system, GABA-mediated inhibition is critical for controlling synaptic circuits involved in the modulation of anxiety [6]. Studies evaluating the anxiety behavior of animals transplanted with cells derived from the MGE [5] and LGE (lateral ganglionic eminence) [7] have shown that these cells can produce anxiolytic-like effects.…”
Section: Introductionmentioning
confidence: 99%